2023
DOI: 10.1371/journal.pone.0280257
|View full text |Cite
|
Sign up to set email alerts
|

No effect of monetary reward in a visual working memory task

Abstract: Previous work has shown that humans distribute their visual working memory (VWM) resources flexibly across items: the higher the importance of an item, the better it is remembered. A related, but much less studied question is whether people also have control over the total amount of VWM resource allocated to a task. Here, we approach this question by testing whether increasing monetary incentives results in better overall VWM performance. In three experiments, subjects performed a delayed-estimation task on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Interestingly, we found little evidence that rewards modulated the probability of binding errors or recall precision. This is consistent with a recent study that found no effect of reward on visual working memory precision (van den Berg et al, 2023). Taken together, these findings indicate that monetary incentives primarily affect whether an item is prioritized for encoding rather than the quality of visual working memory representations or encoding errors (e.g., misbinding of location and feature).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, we found little evidence that rewards modulated the probability of binding errors or recall precision. This is consistent with a recent study that found no effect of reward on visual working memory precision (van den Berg et al, 2023). Taken together, these findings indicate that monetary incentives primarily affect whether an item is prioritized for encoding rather than the quality of visual working memory representations or encoding errors (e.g., misbinding of location and feature).…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies on the effect of motivation on visual working memory capacity and precision have produced mixed results. Some studies have found no effect of reward (van den Berg et al, 2023;Zhang & Luck, 2011), while others have seemingly demonstrated that reward benefits visual working memory performance. However, the observation of a reward effect in these studies generally cannot 16.00 13.86-18.50 15.60 13.81-17.33 14.99 13.33-17.42 Note.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this manipulation, participants should be highly incentivized to focus their available resources on less salient targets to maximize their gains. Recently, it has been called into question, whether reward can increase overall VWM performance (van den Berg et al, 2023), but that reward can affect the distribution of limited cognitive resources among concurrently presented stimuli is well established (reviewed in, e.g., Anderson, 2019) and, in fact, such an effect has been demonstrated also in VWM tasks (Allen & Ueno, 2018; Klink et al, 2017; for a VWM-focused review, see Ravizza & Conn, 2022). As we believe that implementing top-down control takes more than a few hundred milliseconds, we expected (preregistration: https://osf.io/fxwyp) an effect of salience for displays presented for 350 ms.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, visual information is memorized better if it is more likely to be probed (Gorgoraptis et al, 2011; Klyszejko et al, 2014). Likewise, studies have shown that visual information which is associated with higher rewards receives more cognitive resources and is memorized better (Cho et al, 2022; Klyszejko et al, 2014; van den Berg & Ma, 2018; but see van den Berg et al, 2023). Thus, the consequences of actions that are based on VWM content (e.g., correctly reporting the memorized item) seem to influence how well information is memorized or recalled.…”
mentioning
confidence: 99%